Non-thermal microwave effects on chicken foetuses during organogenesis - XENOS (Θ.Δ. ΞΕΝΟΣ) Th. D.; MAGRAS (Ι.Ν. ΜΑΓΡΑΣ) I. N. (Journal of the Hellenic Veterinary Medical Society, 2017)
The purpose of this work is το investigate possible effects of pulse-modulated (PW) and non-modulated (CW) low power density microwave radiation on chicken foetuses during organogenesis. A total of 496 fertilised chicken eggs were used in this study; 380 of diem as experimental material and 116 as controls. The experimental eggs were exposed to a non-thermal power density of 8.8 uW/cm2 (SAR= 1.16 mW/Kg) radiation at 9.152 GHz, from the 3rd to the 10th day of incubation, continuously. 172 eggs were irradiated by CW whereas 208 eggs by PW. The controls were sham-exposed. The foetuses of the experimental eggs and of the controls were macro- and microscopically examined at the end of their incubation. In 62.78% of CW-irradiated, 47.12% of PWirradiated and only in 3.44% of the sham-exposed fetuses abnormalities (development retardation and severe malformations) and embryonic and foetal deaths (embryonic and foetal) were observed. The differences in the effects caused by CW and PW irradiation were statistically evaluated. These results support the aspect that very low power density microwaves applied to the chicken foetuses, in ovo during organogenesis, may cause abnormal development.